A multilayer hybrid high temperature resistant composite lithium negative electrode and its preparation method and application
By coating the colloidal solution of vermiculite sheet on the surface of lithium foil and rolling it, a multi-layer hybrid configuration high-temperature composite lithium negative electrode is formed, which solves the problem of thermal instability of lithium metal batteries at high temperatures, broadens its working temperature range and improves safety.
Patent Information
- Application Number
- CN202410761953.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-13
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-06-13
AI Technical Summary
Lithium metal batteries are limited in use in extreme high temperature environments, mainly due to the low melting point of the lithium negative electrode, which increases safety risks.
By making a colloidal solution of the inorganic high-melting point material vermiculite sheet into a colloidal solution on the surface of the lithium foil, and rolling and pressing, a multi-layer hybrid configuration high-temperature resistant lithium negative electrode is formed.
The melting point of the composite lithium negative electrode is increased, the working temperature of the lithium metal battery is widened to 200℃, and the side reactions and safety problems of electrodes are alleviated at high temperatures.
Smart Images

Figure CN118610416B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery negative electrode materials, and in particular relates to a multi-layer mixed configuration high temperature resistant composite lithium negative electrode and a preparation method and application thereof. Background Art
[0002] Due to the limitation of theoretical energy density of graphite anode, people have focused more on lithium metal batteries (LMBs) with lithium metal as anode. Lithium anode has a very impressive theoretical specific capacity (3860mAh g -1 ), far exceeding the graphite negative electrode, the popularization of lithium negative electrode is bound to greatly improve the energy density of the battery.
[0003] However, Li is located in the second period of the periodic table, group IA, and has active chemical properties. The use of lithium negative electrodes poses a high safety risk. On the one hand, the high reactivity of Li makes it very easy for side reactions to occur with the electrolyte, producing dangerous gases such as H2 and C2H4, causing battery bulging, which in turn causes danger; on the other hand, due to the melting point of lithium metal at 180.5°C and low hardness, it is easy to deform and release heat violently after being squeezed or collided. In addition, most organic electrolytes are flammable, which can easily lead to internal combustion or explosion of lithium batteries.
[0004] In response to these problems, a large number of flame-retardant electrolyte solutions (LHCEs, HFE, etc.) have been developed, and many solid electrolytes (LLZTO, etc.) have also been developed to solve problems such as electrolyte leakage and combustion. However, the low melting point of the lithium negative electrode has not been changed, which limits the use of LMBs in extremely high temperature environments. Currently, there are few reports on high-temperature resistant composite lithium negative electrodes, and the design of high-temperature lithium alloys has also been rarely tested due to low safety and high investment.
[0005] Therefore, how to prepare a lithium negative electrode with high thermal stability has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a multi-layer hybrid high temperature resistant composite lithium negative electrode and a preparation method and application thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a multilayer mixed structure high temperature resistant composite lithium negative electrode, comprising the following steps:
[0009] A vermiculite flake colloidal solution is prepared, the vermiculite flake colloidal solution is coated on one side of a lithium foil and then dried, then rolled with the side coated with the vermiculite flake colloidal solution as the outer layer, and then pressed to obtain the multilayer mixed configuration high temperature resistant composite lithium negative electrode.
[0010] Preferably, the thickness of the vermiculite flakes in the vermiculite flake colloidal solution is 3-100 nm, and the diameter of the flakes is 1-15 μm.
[0011] Preferably, the coating amount of the vermiculite flakes on the lithium foil in the vermiculite flake colloidal solution is (0.5-1) mg / cm 2 .
[0012] Preferably, the preparation method of the vermiculite flakes in the vermiculite flake colloidal solution includes an ion exchange method or an ultrasonic method.
[0013] Preferably, the mass fraction of the vermiculite flakes colloidal solution is 5-15%.
[0014] Preferably, the mass fraction of vermiculite flakes in the rolled composite lithium foil is less than or equal to 40%.
[0015] The present invention provides a multilayer mixed configuration high temperature resistant composite lithium negative electrode prepared by the preparation method described in the above technical solution.
[0016] Preferably, the applicable temperature of the multilayer hybrid high temperature resistant composite lithium negative electrode is -60 to 200°C.
[0017] The present invention also provides the use of the multi-layer mixed configuration high temperature resistant composite lithium negative electrode described in the above technical solution in a lithium battery.
[0018] Compared with the prior art, the present invention has the following advantages and technical effects:
[0019] The present invention prepares an inorganic high melting point material into a colloidal solution and applies it to the surface of lithium foil, and then realizes the composite of the inorganic high melting point material and lithium metal by rolling and pressing, and at the same time forms a multi-layer mixed structure, thereby achieving the purpose of improving the melting point of the composite lithium negative electrode, fundamentally solving the problem of thermal instability of the lithium negative electrode at high temperature, widening the operating temperature of lithium metal batteries (LMBs) to 200°C, and effectively alleviating the electrode side reactions and safety problems caused by collision and extrusion at high temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0021] Figure 1 A schematic diagram of the operation of the method for preparing a multilayer hybrid high temperature resistant composite lithium negative electrode provided by the present invention;
[0022] Figure 2 This is a SEM image of a multilayer hybrid high temperature resistant composite lithium negative electrode prepared in Example 1 of the present invention;
[0023] Figure 3The cycle performance diagram of a full-battery prepared by using the multi-layer hybrid high-temperature resistant composite lithium negative electrode in Example 1 of the present invention at 200°C;
[0024] Figure 4 This is a surface morphology of the negative electrode of a full-electric battery prepared using the multi-layer hybrid configuration high-temperature resistant composite lithium negative electrode in Example 2 of the present invention after charge and discharge cycles. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0027] The embodiment of the present invention provides a method for preparing a multilayer hybrid high temperature resistant composite lithium negative electrode, comprising the following steps:
[0028] A vermiculite flake colloidal solution is prepared, the vermiculite flake colloidal solution is coated on one side of a lithium foil and then dried, then rolled with the side coated with the vermiculite flake colloidal solution as the outer layer, and then pressed to obtain the multilayer mixed configuration high temperature resistant composite lithium negative electrode.
[0029] The present invention prepares a colloidal solution of vermiculite sheets, an inorganic high melting point material, and applies it to the surface of lithium foil, and then realizes the composite of the inorganic high melting point material and lithium metal through rolling and pressing, and at the same time forms a multi-layer mixed structure, so as to achieve the purpose of improving the melting point of the composite lithium negative electrode, fundamentally solve the problem of thermal instability of lithium negative electrode at high temperature, widen the operating temperature of lithium metal batteries (LMBs) to 200°C, and effectively alleviate the electrode side reactions and safety problems caused by collision and extrusion at high temperature.
[0030] In a preferred embodiment, the thickness of the vermiculite flakes in the vermiculite flake colloidal solution is 3-100nm, more preferably 3-50nm; the diameter of the vermiculite flakes in the vermiculite flake colloidal solution is 1-15μm, more preferably 1-5μm. The present invention uses vermiculite flakes with a thickness and a flake diameter within the above range, which have a more uniform dispersion in the colloidal solution, a better adhesion effect on lithium metal, and a more significant effect of improving the melting point of the resulting composite lithium negative electrode.
[0031] In a preferred embodiment, the preparation method of the vermiculite flakes in the vermiculite flake colloidal solution includes an ion exchange method or an ultrasonic method, and more preferably an ion exchange method.
[0032] In a preferred embodiment, the preparation method of the vermiculite flake colloidal solution is: dissolving vermiculite flakes in tetrahydrofuran (THF) to obtain a vermiculite flake dispersion, and then ultrasonicating the vermiculite flake dispersion to obtain the vermiculite flake colloidal solution.
[0033] In a preferred embodiment, the power of the ultrasound is 200 W and the time is 2 hours.
[0034] In a preferred embodiment, the mass fraction of the vermiculite flakes colloidal solution is 5-15%.
[0035] In a preferred embodiment, the coating amount of the vermiculite flakes on the lithium foil in the vermiculite flake colloidal solution is (0.5-1) mg / cm 2 The present invention controls the coating amount of vermiculite flakes on the lithium foil in the vermiculite flake colloidal solution within the above range, which is conducive to obtaining a multi-layer mixed configuration high temperature resistant composite lithium negative electrode with high thermal stability. If the coating amount of vermiculite flakes is too high, the properties of the lithium negative electrode such as capacity and conductivity will be reduced, thereby affecting various performances of the battery.
[0036] In a preferred embodiment, the dry environment is an environment in which the water and oxygen contents are both less than 0.1 ppm, and the equipment is a glove box.
[0037] In a preferred embodiment, the mass fraction of vermiculite flakes in the rolled composite lithium foil is less than or equal to 40%. The present invention forms a multi-layer mixed structure of the composite lithium negative electrode by rolling, and the formed multi-layer mixed structure has the advantages of uniform distribution of vermiculite flakes and firm combination.
[0038] In a preferred embodiment, the pressing temperature is 25°C, the rolling speed is 100 r / min, the set thickness is 0.3-0.6 mm, and the equipment is a roller press. The present invention obtains a multilayer hybrid high temperature resistant composite lithium negative electrode of a desired thickness by pressing.
[0039] The present invention provides a multilayer mixed configuration high temperature resistant composite lithium negative electrode prepared by the preparation method described in the above technical solution.
[0040] In a preferred embodiment, the applicable temperature of the multi-layer hybrid high temperature resistant composite lithium negative electrode is -60 to 200°C.
[0041] The present invention also provides the use of the multi-layer mixed configuration high temperature resistant composite lithium negative electrode described in the above technical solution in a lithium battery.
[0042] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0043] The commercial expanded vermiculite used in the following examples was purchased from Lingshou County Jiayuan Mineral Products Processing Plant.
[0044] Example 1
[0045] A method for preparing a multilayer hybrid high temperature resistant composite lithium negative electrode, the operation diagram is as follows Figure 1 , the specific steps are as follows:
[0046] S1) 200 mg of commercial expanded vermiculite was added to 100 mL of saturated sodium chloride solution, stirred at 120° C. for 24 h, centrifuged, washed with deionized water until there was no chloride ion in the washing solution, freeze-dried at -20° C. for 4 h, and then dried at 120° C. for 24 h to obtain dry two-dimensional vermiculite flakes with a thickness of 10 nm and a layer diameter of 3 μm.
[0047] S2) 100 mg of the dried two-dimensional vermiculite flakes obtained in step S1) were dissolved in THF to obtain a vermiculite flake dispersion with a mass fraction of 5%, and then ultrasonicated at 200 W for 2 h to obtain a stably dispersed vermiculite flake colloidal solution; in a glove box, the obtained vermiculite flake colloidal solution was evenly applied to one side of a lithium foil with a specification of 10 cm×10 cm×0.01 cm (the coating amount of the vermiculite flakes on the lithium foil in the vermiculite flake colloidal solution was 1 mg / cm 2 ), naturally dry for 1 hour, then use the side coated with the vermiculite flake colloidal solution as the outer layer, roll up the lithium foil (the mass fraction of vermiculite flakes in the obtained composite lithium foil is 20%), and then use a roller press to press it into a lithium sheet with a thickness of 0.3 mm, and then use a punching machine to obtain a lithium sheet with a diameter of 12 mm, which is a multi-layer mixed configuration high-temperature resistant composite lithium negative electrode.
[0048] Figure 2 This is a SEM image of the multilayer hybrid high temperature resistant composite lithium negative electrode prepared in Example 1. Figure 2 It can be seen that the surface of lithium metal is uniformly doped with vermiculite flakes.
[0049] The lithium sheet prepared in Example 1 was used as the negative electrode, lithium cobalt oxide was used as the positive electrode, and tantalum-doped lithium lanthanum zirconium oxide (LLZTO) was used as the electrolyte to assemble the full-electric battery B1 in a glove box; the untreated lithium sheet with a diameter of 12 mm and a thickness of 0.3 mm was used as the negative electrode, lithium cobalt oxide was used as the positive electrode, and tantalum-doped lithium lanthanum zirconium oxide (LLZTO) was used as the electrolyte to assemble the full-electric battery B2 in a glove box. B1 and B2 were placed at 200°C and 0.1C for charge and discharge, and their cycle performance was tested. The test was terminated after 8 cycles. The cycle performance was shown in FIG. Figure 3 After the test, the battery was disassembled and it was found that the negative electrode of B1 was intact, while the negative electrode of B2 was severely deformed and could no longer be used.
[0050] Example 2
[0051] A method for preparing a multilayer hybrid high temperature resistant composite lithium negative electrode, the operation diagram is as follows Figure 1 , the specific steps are as follows:
[0052] S1) 200 mg of commercial expanded vermiculite was added to 100 mL of saturated sodium chloride solution, stirred and refluxed at 90° C. for 10 h, centrifuged, and the precipitate was washed with deionized water until there was no chloride ion in the washing solution. The precipitate was added to 1.5 mol / L lithium chloride solution and refluxed at 90° C. for 10 h, centrifuged, and the precipitate was washed with deionized water until there was no chloride ion in the washing solution. The precipitate was then added to 100 mL of 30 wt.% hydrogen peroxide and refluxed at 90° C. for 10 h, then ultrasonicated for 10 h, and then centrifuged at a speed of 4000 r / min for 30 min. Then, the supernatant was taken and centrifuged at a speed of 10000 r / min for 40 min. The precipitate was washed and dried to obtain a dry two-dimensional vermiculite sheet with a thickness of 3 nm and a sheet diameter of 1 μm.
[0053] S2) 100 mg of the dried two-dimensional vermiculite flakes obtained in step S1) were dissolved in THF to obtain a 5% vermiculite flake dispersion, and then ultrasonicated at 200 W for 2 h to obtain a stably dispersed vermiculite flake colloidal solution; in a glove box, the obtained vermiculite flake colloidal solution was evenly applied to one side of a lithium foil having a specification of 20 cm×10 cm×0.01 cm (the coating amount of the vermiculite flakes on the lithium foil in the vermiculite flake colloidal solution was 0.5 mg / cm 2 ), naturally dry for 1 hour, then use the side coated with the vermiculite flake colloidal solution as the outer layer, roll up the lithium foil (the mass fraction of vermiculite flakes in the obtained composite lithium foil is 10%), and then use a roller press to press it into a lithium sheet with a thickness of 0.6 mm, and then use a punching machine to obtain a lithium sheet with a diameter of 12 mm, which is a multi-layer mixed configuration high-temperature resistant composite lithium negative electrode.
[0054] The lithium sheet prepared in Example 2 was used as the negative electrode, NCM ternary was used as the positive electrode, and tantalum-doped lithium lanthanum zirconium oxide (LLZTO) was used as the electrolyte. The full-electric battery B1 was assembled in a glove box. The untreated lithium sheet with a diameter of 12 mm and a thickness of 0.6 mm was used as the negative electrode, NCM ternary was used as the positive electrode, and tantalum-doped lithium lanthanum zirconium oxide (LLZTO) was used as the electrolyte. The full-electric battery B2 was assembled in a glove box. B1 and B2 were placed at 185°C to test their cycle performance. After the test, the battery was disassembled. The negative electrode of B1 was intact, and its surface morphology was as follows: Figure 4 As shown, the negative electrode of B2 is severely deformed and the battery is scrapped.
[0055] Example 3
[0056] A method for preparing a multilayer hybrid high temperature resistant composite lithium negative electrode, the operation diagram is as follows Figure 1 , the specific steps are as follows:
[0057] S1) 200 mg of commercial expanded vermiculite was added to 100 mL of deionized water and stirred to obtain an expanded vermiculite dispersion, and then the vermiculite was exfoliated by ultrasonication for 3 h. After centrifugation, washing and freeze-drying, the vermiculite was dried at 200° C. for 60 h, and then dried at 500° C. for 20 h to obtain dry two-dimensional vermiculite flakes with a thickness of 20 nm and a layer diameter of 5 μm.
[0058] S2) 100 mg of the dried two-dimensional vermiculite flakes obtained in step S1) were dissolved in THF to obtain a vermiculite flake dispersion with a mass fraction of 5%, and then ultrasonicated at 200 W for 2 h to obtain a stably dispersed vermiculite flake colloidal solution; in a glove box, the obtained vermiculite flake colloidal solution was evenly applied to one side of a lithium foil with a specification of 10 cm×10 cm×0.01 cm (the coating amount of the vermiculite flakes on the lithium foil in the vermiculite flake colloidal solution was 1 mg / cm 2 ), naturally dry for 1 hour, then use the side coated with the vermiculite flake colloidal solution as the outer layer, roll up the lithium foil (the mass fraction of vermiculite flakes in the obtained composite lithium foil is 20%), and then use a roller press to press it into a lithium sheet with a thickness of 0.3 mm, and then use a punching machine to obtain a lithium sheet with a diameter of 12 mm, which is a multi-layer mixed configuration high-temperature resistant composite lithium negative electrode.
[0059] The lithium sheet prepared in Example 3 was used as the negative electrode, the NCM ternary was used as the positive electrode, and tantalum-doped lithium lanthanum zirconium oxide (LLZTO) was used as the electrolyte. The obtained full-electric battery was placed at 205°C to test its cycle performance. After the test, the battery was disassembled. The negative electrode was slightly deformed, but the battery structure was still intact.
[0060] Example 4
[0061] A method for preparing a multilayer hybrid high temperature resistant composite lithium negative electrode, the operation diagram is as follows Figure 1 , the specific steps are as follows:
[0062] S1) 200 mg of commercial expanded vermiculite was added to 100 mL of saturated sodium chloride solution, stirred at 100° C. for 48 h, centrifuged, washed with deionized water until there was no chloride ion in the washing solution, freeze-dried at -20° C. for 4 h, then dried at 200° C. for 36 h, and then dried at 500° C. for 10 h to obtain dry two-dimensional vermiculite flakes with a thickness of 100 nm and a layer diameter of 15 μm.
[0063] S2) 100 mg of the dried two-dimensional vermiculite flakes obtained in step S1) were dissolved in THF to obtain a 5% vermiculite flake dispersion, and then ultrasonicated at 200 W for 2 h to obtain a stably dispersed vermiculite flake colloidal solution; in a glove box, the obtained vermiculite flake colloidal solution was evenly applied to one side of a lithium foil having a specification of 20 cm×10 cm×0.01 cm (the coating amount of the vermiculite flakes on the lithium foil in the vermiculite flake colloidal solution was 0.5 mg / cm2 ), naturally dry for 1 hour, then use the side coated with the vermiculite flake colloidal solution as the outer layer, roll up the lithium foil (the mass fraction of vermiculite flakes in the obtained composite lithium foil is 10%), and then use a roller press to press it into a lithium sheet with a thickness of 0.6 mm, and then use a punching machine to obtain a lithium sheet with a diameter of 12 mm, which is a multi-layer mixed configuration high-temperature resistant composite lithium negative electrode.
[0064] The lithium sheet prepared in Example 4 was used as the negative electrode, the NCM ternary was used as the positive electrode, and tantalum-doped lithium lanthanum zirconium oxide (LLZTO) was used as the electrolyte. A full-electric battery was assembled in a glove box. The obtained battery was placed at 210°C to test its cycle performance. After the test, the battery was disassembled and the negative electrode was significantly deformed, and the battery could no longer be used.
[0065] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a multilayer mixed structure high temperature resistant composite lithium negative electrode, characterized in that: The following steps are involved: Prepare a vermiculite flake colloidal solution, apply the vermiculite flake colloidal solution to one side of a lithium foil and then dry it, then roll it with the side coated with the vermiculite flake colloidal solution as the outer layer, and then press it to obtain the multi-layer mixed configuration high temperature resistant composite lithium negative electrode; The thickness of the vermiculite flakes in the vermiculite flake colloidal solution is 3-100 nm, and the diameter of the flakes is 1-15 μm; The preparation method of the vermiculite flakes in the vermiculite flake colloidal solution is as follows: 200 mg of expanded vermiculite is added to 100 mL of saturated sodium chloride solution, stirred at 120° C. for 24 hours, centrifuged, washed with deionized water until there is no chloride ion in the washing solution, freeze-dried at -20° C. for 4 hours, and then dried at 120° C. for 24 hours to obtain dry two-dimensional vermiculite flakes; The mass fraction of the vermiculite sheets in the composite lithium foil obtained by rolling is 10-40%.
2. The method for preparing a multilayer hybrid high temperature resistant composite lithium negative electrode according to claim 1, characterized in that: The coating amount of the vermiculite flakes in the vermiculite flake colloidal solution on the lithium foil is (0.5-1) mg / cm 2 .
3. The method for preparing a multilayer hybrid high temperature resistant composite lithium negative electrode according to claim 1, characterized in that: The mass fraction of the vermiculite flake colloid solution is 5-15%.
4. A multilayered hybrid high temperature resistant composite lithium negative electrode prepared by the preparation method according to any one of claims 1 to 3.
5. The multi-layer hybrid high temperature resistant composite lithium negative electrode according to claim 4, characterized in that: The applicable temperature of the multilayer mixed configuration high temperature resistant composite lithium negative electrode is -60 to 200°C.
6. Use of the multilayer hybrid high temperature resistant composite lithium negative electrode according to any one of claims 4 to 5 in a lithium battery.
Citation Information
Patent Citations
Lithium battery anode and preparation method thereof, and lithium battery
CN110380003A
Method for avoiding thermal runaway of lithium ion battery
CN112332021A